Factors Associated With Attitude-Behavior Conflicts Among Sexually Experienced, Rural, Early Adolescents. (January 2019) - Hill, Julie C.; Graber, Julia A.; Jean-Baptiste, Esther; Johnson, Kelly J.
Adolescents' attitudes predict sexual behavior; therefore, attitudes are targeted in sexually transmitted infection (STI) and pregnancy prevention programs. However, attitudes and behaviors do not always align. Young adolescents who have had penile vaginal intercourse (PVI) and have attitudes supportive of PVI have two risk factors for future health risks while those with attitudes in conflict with PVI experience (i.e., attitudes not supportive of PVI) only have one risk factor, that is, early sexual debut. Rural sixth- to eighth-grade students in southern, central Florida who had PVI experience ( N = 162) completed surveys about their sexual history, substance use, PVI refusal skills, and PVI attitudes. Logistic regressions found that longer time since PVI, never trying other drugs, and better PVI refusal skills predicted higher odds of attitude-behavior conflict; thus, youth with attitude-behavior conflicts have fewer predictors of sexual health risk than those without attitude-behaviors conflicts. Those without attitude-behaviors conflicts likely need more focused and intensive interventions.